Trade and industrial policies : past performance and future prospects (UN SantiagoCL, 1998)
Summarizes the major conclusions of six case studies (Indonesia, The Republic of Korea, Malaysia, Argentina, Brazil and Chile) undertaken and explores possible areas for future policy.
Bibliography: p.49-51